The impact of temperature fluctuations on the large-scale clustering of the Lyα forest - Greig, Bradley; Bolton, James S.; Wyithe, J. Stuart B. (Oxford University Press, 2015)
We develop a semi-analytic method for assessing the impact of the large-scale IGM temperature fluctuations expected following He ii reionization on three-dimensional clustering measurements of the Lyα forest. Our methodology builds upon the existing large volume, mock Lyα forest survey simulations presented by Greig et al. by including a prescription for a spatially inhomogeneous ionizing background, temperature fluctuations induced by patchy He ii photoheating and the clustering of quasars. This approach enables us to achieve a dynamic range within our semi-analytic model substantially larger than currently feasible with computationally expensive, fully numerical simulations. The results agree well with existing numerical simulations, with large-scale temperature fluctuations introducing a scale-dependent increase in the spherically averaged 3D Lyα forest power spectrum of up to 20–30 per cent at wavenumbers k ∼ 0.02 Mpc− 1. Although these large-scale thermal fluctuations will not substantially impact upon the recovery of the baryon acoustic oscillation scale from existing and forthcoming dark energy spectroscopic surveys, any complete forward modelling of the broad-band term in the Lyα correlation function will none the less require their inclusion.